2022
DOI: 10.3390/biology11040539
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of Invertase Gene Family, and Expression Profiling under Abiotic Stress Conditions in Potato

Abstract: The potato is one of the most important and valuable crops in terms of consumption worldwide. However, abiotic stressors are the critical delimiters for the growth and productivity of potato. Invertase genes play key roles in carbon metabolism, plant development, and responses to stress stimuli. Therefore, a comprehensive genome-wide identification, characterization and expression analysis of invertase genes was performed in the potato. The current study identified 19 invertase genes, randomly distributed thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 49 publications
3
23
0
Order By: Relevance
“…Our results are similar to Laware and Raskar (2014) and Abbas et al (2022) reported that onion plants treated with different concentrations of ZnO NPs showed no significant increase in plant height, but the leaf number was significantly increased in all treatments. The highest number, that is, 23.14, was displayed in plants treated with 30-µg ml −1 ZnO NPs compared to control plants.…”
Section: Discussionsupporting
confidence: 92%
“…Our results are similar to Laware and Raskar (2014) and Abbas et al (2022) reported that onion plants treated with different concentrations of ZnO NPs showed no significant increase in plant height, but the leaf number was significantly increased in all treatments. The highest number, that is, 23.14, was displayed in plants treated with 30-µg ml −1 ZnO NPs compared to control plants.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings revealed that when a 125% N rate was applied, morphological and yield traits increased as compared to when a low nitrogen rate was applied ( Figure 2 ). The use of nitrogen has been shown to boost plant height in a variety of crops ( Kumbhar et al, 2008 ; Dong et al, 2010 ; Fahad et al, 2021d ; Abbas et al, 2022 ; Abdelsalam et al, 2022 ). Our results were in line with ( Kumbhar et al, 2008 ; Abdelsalam et al, 2019a ), who indicated that nitrogen has a role in the plant rapid vegetative development and nitrogen deficiency influences the growth and yield of seed cotton.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the wide range of genetic variations among the various accessions of maize, it serves as a model organism for genetic research ( Strable and Scanlon, 2009 ; Afzal et al, 2020 ; Ali et al, 2021 ; Bahar et al, 2021 ; Mahmood et al, 2021 ; Abbas et al, 2022 ). During the previous century, conventional breeding was highly effective at increasing the yield potential of crops, and this was largely accomplished with little knowledge of the factors controlling the genetic variability exploited by breeders, particularly for abiotic tolerance ( Collins et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%